ASSESSING SUCCESS FACTORS OF SOCIAL BUSINESS PERFORMANCE - Rusdianto Rusdianto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This study aims to analyze the factors influencing the success of Village-Owned Enterprises (BUMDes) as a form of social business practice in Indonesia. Drawing on the theoretical framework of dynamic capability, the study highlights the importance of an organization’s ability to sense opportunities, seize them strategically, and transform its institutional structure to remain resilient in a dynamic environment. A qualitative research method was employed, utilizing an exploratory case study approach on two leading BUMDes in the Special Region of Yogyakarta. Data were collected through in-depth interviews, limited observations, and document analysis, and were examined using an interactive analysis model. The findings reveal that BUMDes' success is driven by visionary leadership, adaptability to external dynamics, the enhancement of human resource capacity, transparent financial management, and ecosystem support through collaboration and digital technology. These findings reinforce the relevance of dynamic capability theory in explaining the performance of community-based social enterprises in developing countries and provide both theoretical and practical contributions to the development of policies and strategies for strengthening village economic institutions.